2013
DOI: 10.2478/10004-1254-64-2013-2326
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Zinc Fractionation in Apple Orchard Soil in the Village of Bukevje (Croatia) Using the Revised Four-Step BCR Extraction Procedure

Abstract: The aim of this study was to establish the fractionation of copper and zinc in a small apple orchard using the revised (four-step) Bureau Communautaire de Référence (BCR) sequential extraction procedure and assess their potential mobility in soil. Soil samples were collected at the depth of 10 cm to 25 cm, sixteen from the orchard and fi ve control samples from a meadow located some 200 m away from the orchard. As the distribution of trace-element concentrations in the control samples was normal, they were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…3). Medunić et al [4]; Dabiri et al [29]; Ružičić et al [25]; Bakircioglu et al [30]; and Liu et al [31] found the same orders of Zn fractioning in Cambisol. In soil, zinc forms complexes with organic matter quite quickly, and this has a holding- back effect on the activity of Zn in the soil solution [32].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…3). Medunić et al [4]; Dabiri et al [29]; Ružičić et al [25]; Bakircioglu et al [30]; and Liu et al [31] found the same orders of Zn fractioning in Cambisol. In soil, zinc forms complexes with organic matter quite quickly, and this has a holding- back effect on the activity of Zn in the soil solution [32].…”
Section: Resultsmentioning
confidence: 96%
“…Many previous studies were made to get information about soil accumulation of potentially toxic metals from agriculture. Medunić et al [4] studied the fractionation of copper and zinc in apple orchard soil using sequential extraction procedure. They concluded that copper and zinc are bounded to residual and reducible fractions and their total values do not exceed maximal permissible concentrations (MAC) in agricultural land.…”
Section: Introductionmentioning
confidence: 99%